2021
DOI: 10.1111/his.14430
|View full text |Cite
|
Sign up to set email alerts
|

Combined histopathological risk score using TP53 protein expression, CD8+ T cell density and intratumoral budding is an independent predictor of neoadjuvant therapy response in rectal adenocarcinoma

Abstract: Combined histopathological risk score using TP53 protein expression, CD8 + T cell density and intratumoral budding is an independent predictor of neoadjuvant therapy response in rectal adenocarcinomaAims: Neoadjuvant therapy is the recommended treatment for locally advanced rectal adenocarcinoma; however, there remains significant variability in response to therapy. Tumour protein 53 (TP53) has been associated with therapy response and prognosis with conflicting data. Recently, we demonstrated that immune cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Assessing TB inside the tumor, that is, ITB, yielded results similar to those obtained by evaluating this factor at the invasive front [ 34 ]; thus, ITB could be a prognostic biomarker in PBSs [ 25 ]. Furthermore, ITB in PBSs can play a role in predicting prognosis and the response to neoadjuvant anticancer therapies [ 22 , 23 , 24 , 26 , 27 ]. Moreover, ITB is correlated with poor clinicopathological factors, such as lymph node metastasis, extranodal tumor deposits, local recurrence, distant metastasis, pT stage, and lymphatic and venous invasion [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Assessing TB inside the tumor, that is, ITB, yielded results similar to those obtained by evaluating this factor at the invasive front [ 34 ]; thus, ITB could be a prognostic biomarker in PBSs [ 25 ]. Furthermore, ITB in PBSs can play a role in predicting prognosis and the response to neoadjuvant anticancer therapies [ 22 , 23 , 24 , 26 , 27 ]. Moreover, ITB is correlated with poor clinicopathological factors, such as lymph node metastasis, extranodal tumor deposits, local recurrence, distant metastasis, pT stage, and lymphatic and venous invasion [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Rogers et al classified ITB as being present or absent in 185 patients; however, there was no significant association between ITB and the tumor regression grade [ 23 ]. Nevertheless, Chen et al [ 26 ] and Farchoukh et al [ 27 ] counted the number of TBs per 0.785 mm 2 in 117 patients. They revealed that high-grade ITB (≥2 cells in 0.785 mm 2 ) was significantly associated with tumor regression in univariate [ 26 , 27 ] and multivariate [ 27 ] analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations